A Home-Based Telerehabilitation Program for Patients With Stroke. (October 2017) - Dodakian, Lucy; McKenzie, Alison L.; Le, Vu; See, Jill; Pearson-Fuhrhop, Kristin; Burke Quinlan, Erin; Zhou, Robert J.; Augsberger, Renee; Tran, Xuan A.; Friedman, Nizan; Reinkensmeyer, David J.; Cramer, Steven C.
Background . Although rehabilitation therapy is commonly provided after stroke, many patients do not derive maximal benefit because of access, cost, and compliance. A telerehabilitation-based program may overcome these barriers. We designed, then evaluated a home-based telerehabilitation system in patients with chronic hemiparetic stroke. Methods . Patients were 3 to 24 months poststroke with stable arm motor deficits. Each received 28 days of telerehabilitation using a system delivered to their home. Each day consisted of 1 structured hour focused on individualized exercises and games, stroke education, and an hour of free play. Results . Enrollees (n = 12) had baseline Fugl-Meyer (FM) scores of 39 ± 12 (mean ± SD). Compliance was excellent: participants engaged in therapy on 329/336 (97.9%) assigned days. Arm repetitions across the 28 days averaged 24, 607 ± 9934 per participant. Arm motor status showed significant gains (FM change 4.8 ± 3.8 points, P = .0015), with half of the participants exceeding the minimal clinically important difference. Although scores on tests of computer literacy declined with age ( r = −0.92; P < .0001), neither the motor gains nor the amount of system use varied with computer literacy. Daily stroke education via the telerehabilitation system was associated with a 39% increase in stroke prevention knowledge ( P = .0007). Depression scores obtained in person correlated with scores obtained via the telerehabilitation system 16 days later ( r = 0.88; P = .0001). In-person blood pressure values closely matched those obtained via this system ( r = 0.99; P < .0001). Conclusions . This home-based system was effective in providing telerehabilitation, education, and secondary stroke prevention to participants. Use of a computer-based interface offers many opportunities to monitor and improve the health of patients after stroke.